Modeling and analysis of real-time and embedded systems with UML and MARTE developing cyber-physical systems - Selic, Bran; Gérard, Sébastien (Elsevier, 2014)
Modeling and Analysis of Real-Time and Embedded Systems with UML and MARTE explains how to apply the complex MARTE standard in practical situations. This approachable reference provides a handy user guide, illustrating with numerous examples how you can use MARTE to design and develop real-time and embedded systems and software. Expert co-authors Bran Selic and Sébastien Gérard lead the team that drafted and maintain the standard and give you the tools you need apply MARTE to overcome the limitations of cyber-physical systems. The functional sophistication required of modern
Includes bibliographical references and index
Keywords: UML (Computer science); COMPUTERS / General; Embedded computer systems -- Computer simulation; Echtzeitsystem; Eingebettetes System; UML